Development and validation of HERWIG 7 tunes from CMS underlying-event measurements - (:unkn) unknown (SPRINGER, 2021)
This paper presents new sets of parameters (tunes) for the underlying-event model of the herwig 7 event generator. These parameters control the description of multiple-parton interactions (MPI) and colour reconnection in herwig 7, and are obtained from a fit to minimum-bias data collected by the CMS experiment at v s = 0.9, 7, and 13 TeV. The tunes are based on the NNPDF3.1 next-to-nextto-leading-order parton distribution function (PDF) set for the parton shower, and either a leading-order or next-to-nextto-leading-order PDF set for the simulation of MPI and the beam remnants. Predictions utilizing the tunes are produced for event shape observables in electron-positron collisions, and forminimum-bias, inclusive jet, top quark pair, and Zand Wboson events in proton-proton collisions, and are compared with data. Each of the new tunes describes the data at a reasonable level, and the tunes using a leading-order PDF for the simulation of MPI provide the best description of the data.